2014
DOI: 10.5194/hess-18-3553-2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Utah Energy Balance (UEB) snow model in the Noah land-surface model

Abstract: Abstract. Noah (version 2.7.1), the community landsurface model (LSM) of National Centers for Environmental Predictions-National Center for Atmospheric Research (NCEP-NCAR), which is widely used to describe the landsurface processes either in stand-alone or in coupled landatmospheric model systems, is recognized to underestimate snow-water equivalent (SWE). Noah's SWE bias can be attributed to its simple snow sub-model, which does not effectively describe the physical processes during snow accumulation and mel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Comparison between measured and predicted SWE was similar to previous studies (Marks, Domingo, Susong, et al, ; Sultana, Hsu, Li, & Sorooshian, ). However, model performance at the Prairie site was ranked unsatisfactory.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Comparison between measured and predicted SWE was similar to previous studies (Marks, Domingo, Susong, et al, ; Sultana, Hsu, Li, & Sorooshian, ). However, model performance at the Prairie site was ranked unsatisfactory.…”
Section: Resultssupporting
confidence: 89%
“…This station is at the lowest elevation and lies at the lower fringe of the snow transition zone. For instance, Sultana et al () reported model performance with very low NSC (ranged from 0.1 to 0.9) and high RSR (ranged from 0.28 to 0.86) over 21 SNOTEL sites in California that were mainly located at the rain–snow transition zone (elevation range of 1,500–2,900 m). Mismatch between estimated and observed SWE is due to the following reasons.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding temperature at 10 m depth is at the freezing point and shows no clear trend. ERT is increasingly used in operational permafrost monitoring networks to determine longterm changes in permafrost ice content (Hilbich et al, 2008b(Hilbich et al, , 2011Supper et al, 2014;Doetsch et al, 2015;Pogliotti et al, 2015).…”
Section: Observed Changes In Permafrost and In Rock-glacier Flow Velomentioning
confidence: 99%
“…Current numerical weather prediction systems generally use single-layer snow schemes (IFS documentation, 2016;GFS documentation, 2016). Only in some cases do they explicitly represent the liquid water content within the snowpack, or 15 do they incorporate a refined formulation for snow albedo variability (Dutra et al, 2010;Sultana et al, 2014). Climate models generally resolve the diurnal and seasonal variations of surface snow processes (i.e.…”
Section: Modeling Issues: Spatial Resolution and Physical Processes Imentioning
confidence: 99%